Gene Expression Microarray Data Analysis for Toxicology Profiling - CUNNINGHAM, M. J.; LIANG, S.; FURMAN, S.; SEILHAMER, J. J.; SOMOGYI, R. (Annals of the New York Academy of Sciences, 2000)
: When dealing with thousands of genes, all potentially interesting, it is desirable to rank the genes according to their degree of participation in a physiological process. Therefore, genes with the highest Shannon entropy and ERL can be selected as the best toxicity target candidates, permitting preclinical scientists to focus their research and resources on those genes.